Tunable Q-factor Wavelet Transform for Extraction of Weak Bursts in the Vibration Signal of an Angular Contact Bearing. (2016) - Kumar, Anil; Prakash, Anand; Kumar, Rajesh
Abstract: In this work feature extraction method making use of tunable Q-factor wavelet transform (TQWT) is applied for the ease of detection of bearing defect. Acquired vibration signal is decomposed into various sub-bands using TQWT. Then the signal is reconstructed from the band comprising highest energy. Finally, envelope demodulation of reconstructed signal is carried out. Defect frequency is spotted from the envelope spectrum for identification of defective component in the bearing.